STAINED GLASS ART OF SACRED SPACE IN THE WORKS OF YURIY NOVOSELSKY - РАДОМСЬКА , В. Р. (Art and Design, 2022)
Research purpose is to highlight the practice of designing and implementing stained glass for the sake of forming compositional integrity of interior space design of sacred objects. It will be singled out from the considerable artistic heritage of the proclaimed artist of the XX century Yu. Novoselskyi. Methodology. The methodological basis of the article is established using historical and systematic principle with application of the methods of analysis, statistics, comparison, and generalization. The formal and stylistic analysis is used for clarifying the connection between the modernist artistic practices of Yu. Novoselskyi and the traditional foundations of theological infrastructure formation in sacred space design. Results. The role and significance of stained glass art in decoration of sacred interiors have been revealed. In the context of development of modernist stained glass in sacred space, the set of theological, semantic, artistic, and stylistic features of the project work of the proclaimed artist Yu. Novoselskyi has been determined and analyzed. We have described the explicable influence of modernist fundamentals on interpretation of visual image, which is characterized by inherent compositional and coloristic techniques inspired by modern tendencies of European art with the preservation of unique Byzantine origins. It has been discovered that the conception of theological images and plots, the implementation of deep symbolic content in the new format of interpreting stained glass in the synthesis with traditional functional purpose of sacred interior space of temples of the Eastern rite are the characteristic features of stained glass compositions of Yu. Novoselskyi. Scientific novelty consists in identifying the set of image and stylistic features and consistent patterns of stained glass of Yu. Novoselskyi in organization of interiors with sacred functional purpose. Practical significance. Research results enable the possibility of supplementing the theoretical, scientific, visual, and analogue basis of artistic and design practice, demonstrating the alternative unique approaches in project decisions on the way to establishment and development of modern Ukrainian object-spatial sacred design.